Analysis of malware prediction based on infection rate using machine learning techniques - Zawad, Safir; Mansur, Raiyan; Evan, Nahian; Asad, Ashub Bin (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.